Determinants of Indonesian Public Listed Companies to Participate in the Tax Amnesty - Arie Pratama (Universitas Pasundan, 2018)
This exploratory research paper would investigate several motivations factors that drive the Indonesian public companies to participate in the Tax Amnesty program. The factors were divided into three: Tax Avoidance, Ownership Structures, and Corporate Governance. We also used profitability, size, and age as a control variable. The data collected from public companies listed in Indonesia Stock Exchange. The data will be taken from 2011–2016 companies’ financial statement. There was 135 sample selected using purposive sampling. To analyze the results, we will use binary logistic regressions. The results showed that all the variables mentioned have significant influence toward company's decision to join tax amnesty. The research showed that companies’ decision to participate in Tax Amnesty contribute by many factors, however, in each of the factors, there are different views and perspectives.